Analisis kandungan logam berat timbal (Pb) dan raksa (Hg) pada cat rambut yang beredar di Kota Makassar dengan metode Spektrofotometri Serapan Atom (SSA) - Andi Trihadi Kusuma (Celebes Enviromental Science Journal, 2019)
The A research on the analysis of heavy metal content timbale (Pb) and mercury (Hg) in hair dye circulating in the city of Makassar. This study head to analyze quantitatively the levels of timbale (Pb) and mercury (Hg) in cosmetic hair dye is a metal that is not allowed to use in cosmetic preparation. While the 3 samples analyzed timbale heavy metal content (Pb) and mercury (Hg) by the methode of atomic absorption spectrophotometry (AAS) at a wavelength of 283,3 nm for lead, mercury and to 253,6 nm. Samples in destruction then heated over a water bath. Cooled, after which it’s volume at both end’s meet, then filtered using whatman paper and the filrate is collected. After passing through the destruction proses, the final volume of the sample at both ends meet by adding distilled water. The result of quantitative analysis showed that all samples test negative or does not contain metal timbale (Pb) and mercury (Hg). As know heavy metal can cause interference effect on human health depending on the heavy metals are bound in the body as well as the magnitude of the expose dose.